The novel EGFR mutations (p.E746_S752delinsI, p.T751_I759delinsG, p.L747_S752delinsAA) in patients with non-small cell lung cancer and the clinical treatment strategy: three case reports - Meng, Yamin; Li, Xiaodong; Zhang, Lei; Ye, Minhua (Frontiers in Oncology, 2023)
Epidermal growth factor receptor (EGFR) is an established driver gene in non-small cell lung cancer (NSCLC) and the common Exon 19 del mutation (p.E746_A750 del) has exhibited remarkable responses for EGFR tyrosine kinase inhibitors (TKIs). However, there is even less comprehension of the treatment strategy in NSCLC patients harboring uncommon Exon 19 delins mutation. Here, we identified three novel EGFR Exon 19 mutations (p.E746_S752delinsI, p.T751_I759delinsG, p.L747_S752delinsAA), and described the clinical treatment process. To our knowledge, the EGFR p.E746_S752delinsI mutation of the patient with advanced NSCLC could benefit from the treatment with Icotinib. Otherwise, for the NSCLC patients with early-stage, one harboring p.T751_I759delinsG mutation had an excellent recovery and the other harboring p.L747_S752delinsAA experienced a relapse after receiving horacoscopic radical resection, which means the patients with different Exon 19 delins mutation might have different prognosis. Our study also demonstrated that next-generation sequencing (NGS) is a crucial tool in guiding clinical treatment decisions in NSCLC. Furthermore, the real incidence of these mutation is not known, the routinely use of NGS surely will increase the detection of EGFR del-ins respect to the old tools used to screen for EGFR mutations.